Path to Gender Diversity by 2045: A Strategic Approach - Mishra, Garima (Digital Repository of Theses, 2024)
This comprehensive research evaluates the trajectory of gender diversity in the business sector with a focus on predicting the anticipated male-to-female ratio by 2045. Employing a mixed-methods approach, the research integrates both quantitative and qualitative data, drawing on the Theory of Change and the Theory of Constraints to understand the dynamics of workplace gender representation. Quantitative data analysis includes a thorough assessment of historical gender diversity statistics from various industries, utilizing global labor force surveys, corporate diversity reports, academic publications, and government statistics. Qualitative insights are derived from 20 structured interviews with senior executives and HR leaders, coupled with a survey of 200 professionals from diverse industries and demographics. The research's quantitative findings reveal a consistent increase in female workforce participation, yet the current pace of progress is insufficient to meet the 2045 gender parity goal without significant acceleration. Structural barriers such as entrenched biases, lack of mentorship, and inadequate organizational support remain significant challenges. Content analysis from interviews highlights the limited effectiveness of existing diversity initiatives due to these systemic obstacles. Correlation analysis demonstrates a robust positive relationship between the perceived benefits and drawbacks of gender balance. This indicates a consistent acknowledgment of the significance of gender diversity across various demographics. Regression analysis pinpoints key factors impacting gender balance, including the necessity for comprehensive diversity strategies, strong leadership, and supportive workplace policies. The research underscores the necessity of proactive and inclusive workplace cultures, rigorous enforcement of hiring and promotion quotas, and continuous monitoring and adaptation of diversity initiatives. It recommends leveraging theoretical frameworks like the Theory of Change and the Theory of Constraints to identify and overcome barriers, promoting a strategic approach to achieving gender parity. The findings suggest cautious optimism towards achieving gender parity by 2045, provided significant improvements are made in corporate diversity strategies. This contributes valuable insights for policymakers, business leaders, and diversity advocates, emphasizing the need for substantial changes in organizational practices to foster a more inclusive and equitable workforce. The economic and social benefits of gender diversity are highlighted, underscoring its role in enhancing organizational performance and driving inclusive economic growth.